2001
DOI: 10.1097/00004872-200102000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy and nocturnal hypoxemia in hemodialysis patients

Abstract: Nocturnal hypoxemia is an important correlate of LVH in hemodialysis patients. Such an association is largely independent of arterial pressure. These data further underscore the importance of disturbed respiratory control as a cardiovascular risk factor in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 35 publications
0
35
0
3
Order By: Relevance
“…In MHD patients, it has been demonstrated that impaired sleep may worsen the cardiovascular profile [4]and may negatively affect the immune system function [5], thus influencing the two leading causes of death of uremic patients. The possibility to cure some of the dialysis-related problems causing insomnia such as pruritus, bone pain, and congestive heart failure and the availability of new hypnotics which associate a good clinical response with minor side effects open new encouraging perspectives to the nephrologist in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In MHD patients, it has been demonstrated that impaired sleep may worsen the cardiovascular profile [4]and may negatively affect the immune system function [5], thus influencing the two leading causes of death of uremic patients. The possibility to cure some of the dialysis-related problems causing insomnia such as pruritus, bone pain, and congestive heart failure and the availability of new hypnotics which associate a good clinical response with minor side effects open new encouraging perspectives to the nephrologist in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients with ESRD have shown that nocturnal hypoxemia is associated with left-ventricular hypertrophy (6), coronary artery disease (3), and a higher risk for cardiovascular events (7). However, limited evidence exists as to whether sleep disorders increase the risk for death in patients with ESRD.…”
mentioning
confidence: 99%
“…Therefore, autonomic dysfunction in ESRD may be considered another facet of the complex cardiovascular sequelae of nocturnal hypoxemia. Nocturnal hypoxemia in dialysis patients is also associated with nocturnal hypertension [31] and even more strongly with concentric hypertrophy and remodeling [32]. Thus, several intermediate mechanisms may conjure in determining the adverse cardiovascular outcomes of SA we observed in dialysis patients.…”
Section: Cardiovascular Sequelae Of Sa In Esrdmentioning
confidence: 72%